Physical Characteristics Of Garut Starch Based Edible Film With The Addition Of Aloe Vera Gel (Aloe Vera) - Masru’ah, Sallwa Asrofil; Warkoyo, Warkoyo (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2023)
Packaging technology in the form of starch-based edible film has been widely discovered and developed at present, one of which is Edible Film Pati Garut. Arrowroot starch has a starch content of 98.1% and is classified as high. The addition of aloe vera gel is known to inhibit the transfer of CO2 and O2 gases and contains many functional components that are able to inhibit damage to a product so it is hoped that it can improve the physical characteristics of the resulting film. This research aims to determine the effect of adding arrowroot starch and aloe vera gel on the characteristics of edible films, to determine the effect of differences in arrowroot starch concentrations on film characteristics, to determine the effect of differences in aloe vera gel concentrations on film characteristics and to determine the best treatment for adding arrowroot starch concentrations and aloe vera gel concentration on physical characteristics. This research used a factorial Randomized Group Design (RAK) method with 2 factors. The first factor is the concentration of arrowroot starch (A) (4%, 5% and 6%) and the second factor is the concentration of aloe vera gel (B) (3%, 4% and 5%) to obtain 9 treatment combinations with 3 repetitions. . The parameters observed included thickness analysis, transparency. The results of the study showed that there was no interaction between arrowroot starch concentration and aloe vera gel concentration on physical characteristics. The addition of arrowroot starch concentration has a significant effect on the thickness and transparency values. The addition of aloe vera gel concentration has a significant effect on the thickness and transparency values. The best treatment in this study was the A3B3 treatment (6% arrowroot starch concentration and 5% aloe vera gel) with an average value What was obtained was a thickness of 0.17 mm and a transparency of 2.162 (A546 mm).